THE HISTORY OF VISUAL ART AND ITS CONTEMPORARY RELEVANCE: EVOLUTION, INFLUENCE, AND PEDAGOGICAL IMPLICATIONS - Barchinoy Kurbonova Mirzahamdamovna (Web of Journals Publishing, 2025)
This article provides a comprehensive examination of the historical development of visual art and its sustained relevance in the context of 21st-century culture, education, and digital innovation. By tracing artistic evolution from prehistoric cave paintings to contemporary digital installations, the study emphasizes how visual art reflects sociocultural dynamics and contributes to human cognition, identity, and communication. Drawing from Scopus-indexed scholarly sources, historical records, and educational frameworks, the article critically evaluates the role of visual art in modern society and its integration into interdisciplinary and technological learning environments.
Keywords: Visual art history, contemporary art, cultural heritage, artistic education, digital humanities, aesthetic cognition, interdisciplinarity.